2021
DOI: 10.31051/1852.8023.v13.n1.30811
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Body Donation Among the Population of Cordoba in Argentina

Abstract: Corpses are an irreplaceable resource for teaching and research in Anatomy. Voluntary donation is the source of cadavers, but in the  National University of Cordoba we are struggling with a critical shortage due to the lack of an organized donation program. The objective of this study was to know the attitude of general population of the city of Cordoba about this subject and the profile of potential donors to develop a program. A survey was randomly distributed among older than 18 years. The questionnaire inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The National University of Cordoba in Argentina, only receives donated bodies; however, limited donations have resulted in a critical shortage that has placed both education and research at risk (Biasutto et al 2021 ). Biasutto et al ( 2021 ) surveyed thousands of individuals living in Cordoba and identified that cultural, religious, and inadequate public information might be implicated in the shortage of donors.…”
Section: South Americamentioning
confidence: 99%
“…The National University of Cordoba in Argentina, only receives donated bodies; however, limited donations have resulted in a critical shortage that has placed both education and research at risk (Biasutto et al 2021 ). Biasutto et al ( 2021 ) surveyed thousands of individuals living in Cordoba and identified that cultural, religious, and inadequate public information might be implicated in the shortage of donors.…”
Section: South Americamentioning
confidence: 99%